The Development of WhatsApp-Based Technology Products Using the Design Thinking Approach : Case Study of Finpay Link at PT Finnet Indonesia - Roosdiono Roosdiono; Astri Ghina (International Journal of Economics and Management Sciences, 2025)
Finpay Link, developed by PT Finnet Indonesia, is a unique URL generated by the Finpay Payment Gateway system to facilitate payment transactions via email, SMS, or messaging apps like WhatsApp. Designed to simplify transactions for MSMEs, it aims to contribute significantly to the company’s revenue through increased business transactions. However, since its launch in 2019, Finpay Link has not met the expected revenue targets, prompting the need for new innovations based on the existing product. Given the high adoption of WhatsApp in Indonesia, with 90.9% of social media users active on the platform, this study explores the design and development of a WhatsApp-based application using the design thinking approach. Aimed at MSMEs, this application is intended to drive business transactions and revenue. This qualitative case study employs observation and in-depth interviews for data collection. The study results include the design of new features like payment processing and transaction history tracking. Prototype testing using the System Usability Score (SUS) yielded an 89.5 score, indicating high usability. Positive feedback from users confirmed the value of the payment and transaction tracking innovations. Despite time limitations, this research provides a foundation for future enhancements and can serve as a reference for applying design thinking in business app development.